Programming of glucose–insulin homoeostasis: long‐term consequences of pre‐natal versus early post‐natal nutrition insults. Evidence from a sheep model. (22nd March 2013) - Kongsted, A. H.; Tygesen, M. P.; Husted, S. V.; Oliver, M. H.; Tolver, A.; Christensen, V. G.; Nielsen, J. H.; Nielsen, M. O.
Abstract Aim Exposure to adverse intra‐uterine conditions can predispose for metabolic disorders later in life. By using a sheep model, we studied (i) how programming of glucose–insulin homoeostasis during late gestation is manifested later in life depending on the early post‐natal dietary exposure and (ii) whether dietary alteration in obese individuals can prevent adverse outcomes of early life programming. Methods During late gestation, twin‐pregnant sheep were fed 100% (NORM) or 50% (LOW) of energy and protein requirements. After birth, offspring were exposed to a moderate (CONV) or high‐carbohydrate–high‐fat (HCHF) diet until around puberty. Offspring remaining thereafter (exclusively females) were fed a moderate diet until young adulthood. Results LOW lambs had increased insulin secretory responses during intravenous glucose tolerance tests indicative of reduced insulin sensitivity. HCHF lambs were hypertriglyceridaemic, 75% had mild pancreatic collagen infiltration, and their acute insulin secretory response and insulin clearance during intravenous glucose and insulin tolerance tests, respectively, were reduced. However, NORM‐HCHF in contrast to LOW‐HCHF lambs had normal glucose tolerance, indicating that later health outcomes are highly influenced by pre‐natal nutrition. Dietary alteration normalized glucose–insulin homoeostasis in adult HCHF females, whereas late‐gestation undernutrition (LOW) permanently depressed insulin sensitivity. Conclusion Maintenance of glucose tolerance in sheep exposed to pre‐natal undernutrition relied on pancreatic hypersecretion of insulin to compensate for reduced insulin sensitivity. A mismatching high‐fat diet in early post‐natal life interfered with this pancreatic hypersecretion resulting in reduced glucose tolerance. Early post‐natal, but not late pre‐natal, impacts on glucose–insulin homoeostasis could be reversed by dietary correction later in life.